La marca territorial de la parroquia Oyacachi, provincia de Napo, su relación con el posicionamiento deseado y construcción gráfica. - Parión Pilca, Emanuel Héctor (2023)
Territorial brands can expose to society the differential attributes of a place, based on the natural and cultural attractions, history, and values of the sector, etc. thus allowing the generation of a new destination image in the public. For this reason, the present research work aims to build the identity of the territorial brand of the Oyacachi parish, Napo province, based on a clear and coherent identifying sign for its local positioning; in this sense, the research has a qualitative, descriptive, and non-experimental approach, given that a documentary investigation was applied through bibliographic sources and focus groups to gather information and develop the brand. In addition, the methodology of the Studio A model was used for the construction of the imagotype of the Oyacachi parish; through the brand it is intended to make known the natural and cultural attractions to the national and foreign population since it is little known because it is located very far from Quito city, which is why it will be promoted through digital media. Therefore, the beneficiaries will be the people who are dedicated to tourism, for example: lodging, gastronomy, handicrafts, etc.